2020
DOI: 10.1177/1356766720904773
|View full text |Cite
|
Sign up to set email alerts
|

You exist in my song! How a destination-related popular song enhances destination image and visit intentions

Abstract: Research on media-induced tourism has been growing in recent years. The existing research has shown that films, television programs, and radio commercials can induce tourism behavior. The present research aimed to introduce a new form of music-induced tourism to the literature by examining the impact of a destination-related popular song on prospective tourists’ intentions to visit the destination. A theoretical model that included music-evoked mental imagery, affective image, overall image, and visit intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 99 publications
(152 reference statements)
3
15
0
Order By: Relevance
“…The results are consistent with prior studies (Pan and Hanusch, 2011; Trompeta et al , 2022; Yin et al , 2020), positing that music conveys meaning directly and indirectly. Music alludes a destination’s character because audiences associate its structural elements with different features of the destination and the association shapes their image of the city.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results are consistent with prior studies (Pan and Hanusch, 2011; Trompeta et al , 2022; Yin et al , 2020), positing that music conveys meaning directly and indirectly. Music alludes a destination’s character because audiences associate its structural elements with different features of the destination and the association shapes their image of the city.…”
Section: Discussionsupporting
confidence: 91%
“…The present exploratory study investigated the roles of music in DPVs. In line with previous literature (Hadinejad et al, 2019;Lantos and Craton, 2012;Yin et al, 2020), music in short DPVs proved effective in stimulating cognitive and affective responses. Advancing current knowledge in tourism marketing, empirical support is provided for the notion that music in DPVs has the capacity to both gain and retain audience attention and interest, through structural elements such as tempo, rhythm and dynamics.…”
Section: Discussionsupporting
confidence: 89%
“…Affective image shows an individual’s feelings and emotional responses toward a destination ( Baloglu and Brinberg, 1997 ). In addition, scholars have agreed that every place has an overall image, which refers to people’s general impressions of a destination ( Baloglu and McCleary, 1999 ; Yin et al, 2020 ). Finally, a conative image is akin to action or behavior ( Pike and Ryan, 2004 ; Casali et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the residents’ perspective, the destination image is also significantly related to the attitude toward tourism development and pro-tourism behavior ( Shen et al, 2019 ). Previous studies have successfully demonstrated destination image models containing different elements (cognitive, affective, overall, and conative image) under different research settings ( Agapito et al, 2013 ; Hernández-Mogollón et al, 2018 ; Yin et al, 2020 ). However, these models may not be simply applied to multi-destination tourism because each destination city has unique characteristics that constitute its cognitive image.…”
Section: Introductionmentioning
confidence: 99%
“…Today, in the context of the rapid evolution of economic growth, individuals have a growing need for a better life, the demand for cultural and entertainment consumption has risen to a higher level, and interactive experience has become the core requirement of film watching in the new age. The individuals are no longer limited to visual and audio enjoyment, but in the pursuit of collision of psychology and emotion, and the empathy of local cuisines, song, film, and television has become the key factor for the success of destination management (Li and Katsumata, 2020 ; Yin et al, 2020 ; Cao et al, 2021 ; Yi et al, 2022 ). Specifically, a large number of films watching evaluation feedbacks show that the effective empathy communication system presented by the film contents not only ensures effective transmission of the film's popularity but also improves economic and social benefits (Griffin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%